1992
DOI: 10.1242/jeb.172.1.193
|View full text |Cite
|
Sign up to set email alerts
|

The osteoclast proton pump differs in its pharmacology and catalytic subunits from other vacuolar H+-ATPases

Abstract: Osteoclasts are multinucleated cells derived from the mononuclear phagocyte system in the hematopoietic bone marrow. Their function is to resorb bone during skeletal growth and remodeling. They perform this function by acidifying an enclosed extracellular space, the bone resorbing compartment. Analysis of proton transport by inside-out vesicles derived from highly purified chicken osteoclast membranes has revealed the presence of a novel type of multisubunit vacuolar-like H(+)-ATPase. Unlike H(+)-ATPases deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…52 BAF binds to the Vo subunits of V-ATPase to inhibit bone resorption activity, which results in OC apoptosis and the impairment of OC endocytosis. 53 BAF suppresses the expression of NF-κB and NFAT during RANKL-induced OC differentiation, resulting in smaller and fewer OC nuclei, due to increased p62 expression. 30 In our study, BAF treatment reduced the number of OCs produced by M-CSF and RANKL treatment, and increased CTSK and NFATc1 expression, which is inconsistent with the results reported by Cai et al 54 CTSK is a lysosomal cysteine protease capable of cleaving the helical and telopeptide regions of type I collagen during OC differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 BAF binds to the Vo subunits of V-ATPase to inhibit bone resorption activity, which results in OC apoptosis and the impairment of OC endocytosis. 53 BAF suppresses the expression of NF-κB and NFAT during RANKL-induced OC differentiation, resulting in smaller and fewer OC nuclei, due to increased p62 expression. 30 In our study, BAF treatment reduced the number of OCs produced by M-CSF and RANKL treatment, and increased CTSK and NFATc1 expression, which is inconsistent with the results reported by Cai et al 54 CTSK is a lysosomal cysteine protease capable of cleaving the helical and telopeptide regions of type I collagen during OC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Bafilomycin, a late‐stage lysosome inhibitor, could prevent lysosome‐autophagosome fusion, causing autophagic flux disruption . BAF binds to the Vo subunits of V‐ATPase to inhibit bone resorption activity, which results in OC apoptosis and the impairment of OC endocytosis . BAF suppresses the expression of NF‐κB and NFAT during RANKL‐induced OC differentiation, resulting in smaller and fewer OC nuclei, due to increased p62 expression .…”
Section: Discussionmentioning
confidence: 99%
“…We found that a high-quality crystal was obtained at pH 8.5 using the hanging drop method, and we determined its crystal structure at 1. 4 A resolution (Fig. 1, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…During bone destruction, an acidic environment is formed in bone lacunae. This is primarily due to the active secretion of protons through the osteoclastic V-ATPase and by the passive flow of chloride ions through the chloride channel ClC-7 in the osteoclast-bone interface (4)(5)(6)(7). The low pH conditions are essential for the dissolution of hydroxyapatite (8)(9)(10).…”
mentioning
confidence: 99%